Taxonomic significant of leaf anatomical characteristics of selected Globba L. (Zingiberaceae) species in Peninsular Malaysia - Talip, Noraini; Basir, Syazwani; Che Amri, Che Nurul Aini; Ghazalli, Mohd Norfaizal; Zohari, Ahmad Fitri; Ahmad Juhari, Muhammad Amirul Aiman; Abdul Rahman, Mohamad Ruzi; Bunawan, Hamidun (Penerbit Universiti Sains Malaysia, 2025)
A comparative leaf anatomy study was carried out on 10 taxa of Globba L. (Zingiberaceae) in Peninsular Malaysia to ascertain their systematic significance, especially for species differentiation and identification. Methods used include leaf clearing, leaf sectioning using a sliding microtome and observation under a scanning electron microscope. Results 3 showed that a combination of the following characters have taxonomic significance in Globba spp. studied i.e. outlines of leaf margin, midribs, petioles and their relative sizes; number of vascular bundles in arc I, II, III and IV in the midribs and petioles; absence or presence and type of trichomes; presence of fibre caps and girders in vascular bundles in the leaf lamina, as well as the presence of hypodermal layers below adaxial epidermis. Anatomical characteristics such as tufted trichomes in G. patens, papilose adaxial epidermal cells in G. variabilis var. pusilla, rounded margin in G. variabilis and an arc I vascular bundle present only in the midrib of G. variabilis var. pusilla can be used as diagnostic characters for each species. Globba variabilis var. pusilla which is closely related to G. variabilis can be distinguished by the papilose epidermal cells. This study proved that leaf epidermis anatomical characteristics could possibly be applied to the identification of some species in Globba with certainty.